INSTITUTIONAL AND GENDER DIFFERENCES IN THE KNOWLEDGE AND ATTITUDE OF OYO STATE TERTIARY INSTITUTION STUDENTS TOWARDS HIV/AIDS - Adeoye, E. A.; Awoniyi, G. F. (Sokoto Educational Review, 2011)
A study on attitude towards HIV/AIDS and people living with AIDS (PLWA) seem to be necessary for the view of the current stigma attached to both the disease and the PLWAS. Therefore, this study was carried out among tertiary institutions students in Oyo state in order to assess their knowledge of and attitude towards HIV/AIDS. Data was collected with the use of a structural questionnaire. Purposive sampling technique was used to select three institutions from the three senatorial districts in the state, 750 completed questionnaire forms were returned to the researchers. Data were analysed using t-test and analysis of variance, (ANOVA). Two of the hypotheses (1x2) were accepted while hypotheses 3 and 4 were rejected. Also, gender did not differentiate the attitude of the respondents as a had aversion towards HIV/AIDS as well as people living with AIDS. It was recommended that the governments (Federal, States and Local governments) should incorporate in their education policy, counselling services, sex education and HIV/AIDS education for tertiary institution students so as to improve on the attitude of educated young people towards HIV/AIDS patients. It was also recommended that teachers, school authorities, curriculum planners, religions organizations, health professionals, health educators, AIDS campaigners, governments (Federal, States and Local governments), Non-Governmental Organizations (NGO’s) and the society at large should be involved in the enlightenment programme to appropriately assist even the educated, people such as tertiaiy institution students to imbibe accommodating attitudes towards AIDS and those people living with HIV/AIDS in Nigeria. Tertiaiy institution students to imbibe to accommodating attitudes towards AIDS and those people living with HIV/AIDS in Nigeria.